2020
DOI: 10.1002/tbio.201900032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Ruthenium coordination complex as photosensitizer for PDT of bladder cancer: Cellular response, tissue selectivity and in vivo response

Abstract: TLD1433, a Ru(II) polypyridyl complex, was recently introduced. It can be activated in the 520 to 540 nm range. Here we report on the use of TLD1433 for the treatment of bladder carcinomas in vitro and in an in vivo orthotopic model. The electrostatic properties of the normal urothelium vs a tumor compromised urothelium provide for a high selective uptake ratio. In vitro, a 1000 difference in the LD 50 between dark and 22.5 J cm −2 irradiation at 530 nm was achieved for two bladder cell lines (T24 and AY-27). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In conclusion, the preclinical studies 26 showed that TLD-1433 for NMIBC presents with a considerable SUR of 192. PDT treatment selectivity needs to ensure the threshold for the tumor being exceeded across the bladder wall but not for the normal urothelium.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In conclusion, the preclinical studies 26 showed that TLD-1433 for NMIBC presents with a considerable SUR of 192. PDT treatment selectivity needs to ensure the threshold for the tumor being exceeded across the bladder wall but not for the normal urothelium.…”
Section: Discussionmentioning
confidence: 82%
“…PDT treatment selectivity needs to ensure the threshold for the tumor being exceeded across the bladder wall but not for the normal urothelium. The worst-case estimate for the threshold values reported 26 one that needs 13.2 times more photons to be absorbed in the tumor compared to the urothelium and detrusor muscle, respectively, to achieve selectivity. Selectivity between the tumor and the muscle is independent of light attenuation across the bladder mucosa, whereas selectivity between tumor and urothelium needs to consider the differences in fluence across the mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,48,[53][54][55][56][57][58][59][60][61] Our TLD1433 is one example, which is a bisheteroleptic Ru(II) complex based on the a-terthienylappended imidazo [4,5-f] [1,10]phenanthroline (IP-3T) ligand that generates 1 O 2 with almost unity efficiency. 16,17,48,[62][63][64][65][66] TLD1433 is the rst Ru(II) complex to enter a human clinical trial and is being evaluated in a Phase 2 clinical trial for treating non-muscle invasive bladder cancer with PDT (Clinicaltrials.gov identier: NCT03945162). 16,17,66 Our ongoing interest in exploring the photoreactivity of Ru(II) metal-organic systems, including TLD1433, inspired the present study.…”
Section: Introductionmentioning
confidence: 99%